THE PROCESS OF DISCOVERING STUDENT’S CONJECTURE IN ALGEBRA PROBLEM SOLVING - Yuniati, Suci; Nusantara, Toto; Subanji, Subanji; Sulandra, I Made (International Journal of Insights for Mathematics Teaching (IJOIMT), 2018)
This exploratory descriptive research aims to describe the process of discovering student?s conjecture in mathematics problem solving. There were 2 students in grade VII of Junior High School who participated as the research subject. The instruments used in this research were problem solving test and interview. This research consisted of three stages which were: 1) data collection; data taken process where the researcher asked every student to solve the problem given; 2) analysis on students? work and interview; in this step the researcher analyzed the results of the students? work and carried out interview with the students for further examination of conjecture discovering process when solving the problem; and 3) examining and concluding students? work result and interview result. The result of this study shows that the stages in discovering conjecture were done sequentially although not all steps were done.